Deskripsi Profil dan Minat Belajar Bahasa Indonesia melalui Asesmen Diagnostik pada Siswa Kelas 1 Sekolah Dasar - Ady Saputra; Mety Toding Bua; Sulfa Sulfa (ARZUSIN, 2025)
Diagnostic assessment is a crucial tool for gathering initial information about students’ learning needs, particularly for targeted instructional planning. Elementary school teachers require accurate data regarding students’ learning profiles and interests in Indonesian language learning, especially in early reading skills. This study aims to describe the learning profiles and interests of first-grade elementary students in Indonesian language learning. A descriptive qualitative approach was employed, involving 56 student participants. Data were collected through diagnostic assessments consisting of early reading skill tests, interview sheets, and observations. Data collection techniques included testing, observation, and interviews. The findings reveal that in early reading skills, students made 68 errors in reading letters, 96 errors in reading syllables, and 287 errors in reading words. In terms of learning interest, 89% of students expressed enjoyment in reading, although 51% still struggled with maintaining a consistent reading routine. The study concludes that first-grade students have diverse learning profiles and interests in Indonesian language learning. The implications suggest that the information gathered from this diagnostic assessment can be utilized by teachers to design more effective, adaptive, and individually responsive instruction.